A Novel Occulta-Type Spina Bifida Mediated by Murine Double Heterozygotes EphA2 and EphA4 Receptor Tyrosine Kinases - Abdullah, Nor Linda; Mohd-Zin, Siti W.; Ahmad-Annuar, Azlina; Abdul-Aziz, Noraishah M. (Frontiers in Cell and Developmental Biology, 2017)
Members of the Eph receptor tyrosine kinase have previously been implicated in cranial neural tube development. Failure of neural tube closure leads to the devastating conditions known as anencephaly and spina bifida. EphA2 and EphA4 are expressed at the tips of the closing spinal neural folds prior and during neural tube closure. We investigated the possible role of murine EphA2 and EphA4 during the last step of primary neural tube closure, which is adhesion and fusion. The individual mouse knockouts of EphA2 and EphA4 per se do not exhibit neural tube defects (NTDs). The embryos generated by the crossing of double heterozygotes Epha2tm1Jrui/+Epha4rb-2J/+ displayed NTDs with a wide degree of severity including close exencephaly and close spina bifida (spina bifida occulta). Interestingly, mutants displaying NTDs had skin covering the underlying lesion. The tissue sections revealed the elevated neural folds had not adhered and fused. The phenotypes seen in Epha2tm1Jrui/+Epha4rb-2J/+ double heterozygous embryos suggest both genes play a compensatory role to each other in the adhesion and fusion of the neural tube. In this study, there exists a greater than 50% penetrance of NTDs in the mouse mutants, which genetically have a single allele each of EphA2 and EphA4 absent.